Oxidative stabilization of polyacrylonitrile nanofibers and carbon nanofibers containing graphene oxide (GO): a spectroscopic and electrochemical study - Gergin, İlknur; Ismar, Ezgi; Sarac, A. Sezai (Beilstein Journal of Nanotechnology, 2017)
In this study, a precursor for carbon nanofibers (CNF) was fabricated via electrospinning and carbonized through a thermal process. Before carbonization, oxidative stabilization should be applied, and the oxidation mechanism also plays an important role during carbonization. Thus, the understanding of the oxidation mechanism is an essential part of the production of CNF. The oxidation process of polyacrylonitrile was studied and nanofiber webs containing graphene oxide (GO) are obtained to improve the electrochemical properties of CNF. Structural and morphological characterizations of the webs are carried out by using attenuated total reflectance Fourier transform infrared spectroscopy and Raman spectroscopy, scanning electron microscopy, atomic force microscopy and transmission electron microscopy. Mechanical tests are performed with a dynamic mechanical analyzer, and thermal studies are conducted by using thermogravimetric analysis. Electrochemical impedance spectroscopy, and cyclic voltammetry are used to investigate capacitive behavior of the products. The proposed equivalent circuit model was consistent with charge-transfer processes taking place at interior pores filled with electrolyte.
Keywords: carbon nanofiber; graphene oxide; oxidized polyacrylonitrile (PAN)

(untitled) - Wu, Q.; Xu, Y.; Yao, Z.; Liu, A.; Shi, G. (ACS Nano, 2010)

(untitled) - Vieira, R.; Pham-Huu, C.; Keller, N.; Ledoux, M. J. (Chem. Commun., 2002)

(untitled) - Tamura, T.; Kawakami, H. (Nano Lett., 2010)

(untitled) - Li, D.; Xia, Y. (Adv. Mater., 2004)

(untitled) - Green, K. J.; Dean, D. R.; Vaidya, U. K.; Nyairo, E. (Composites, Part A, 2009)

(untitled) - Sadeghian, R.; Gangireddy, S.; Minaie, B.; Hsiao, K.-T. (Composites, Part A, 2006)

(untitled) - Tibbetts, G. G.; Lake, M. L.; Strong, K. L.; Rice, B. P. (Compos. Sci. Technol., 2007)

(untitled) - Rodriguez, A. J.; Guzman, M. E.; Lim, C.-S.; Minaie, B. (Carbon, 2011)

(untitled) - Ko, T.-H. (J. Appl. Polym. Sci., 1991)

(untitled) - Shokuhfar, A.; Sedghi, A.; Farsani, R. E. (Mater. Sci. Technol., 2006)

(untitled) - Yusof, N.; Ismail, A. F. (J. Anal. Appl. Pyrolysis, 2012)

(untitled) - Dalton, S.; Heatley, F.; Budd, P. M. (Polymer, 1999)

(untitled) - Faraji, S.; Yardim, M. F.; Can, D. S.; Sarac, A. S. (J. Appl. Polym. Sci., 2017)

(untitled) - Rahaman, M. S. A.; Ismail, A. F.; Mustafa, A. (Polym. Degrad. Stab., 2007)

(untitled) - Arshad, S. N.; Naraghi, M.; Chasiotis, I. (Carbon, 2011)

(untitled) - de Almeida Coelho, N. M.; Furtado, J. L. B.; Pham-Huu, C.; Vieira, R. (Mater. Res. (Sao Carlos, Braz.), 2008)

(untitled) - Lee, S.; Kim, J.; Ku, B.-C.; Kim, J.; Joh, H.-I. (Adv. Chem. Eng. Sci., 2012)

(untitled) - Ismar, E.; Sarac, A. S. (Polym. Adv. Technol., 2016)

Carbon Fibers and Their Composites - Morgan, P. (Taylor & Francis, 2005)

Acrylic Fiber Technology and Applications - Masson, J. (CRC Press, 1995)

(untitled) - Devasia, R.; Nair, C. P. R.; Sivadasan, P.; Katherine, B. K.; Ninan, K. N. (J. Appl. Polym. Sci., 2003)

(untitled) - Kakida, H.; Tashiro, K.; Kobayashi, M. (Polym. J., 1996)

(untitled) - Lee, S.; Kim, Y.-J.; Kim, D.-H.; Ku, B.-C.; Joh, H.-I. (J. Phys. Chem. Solids, 2012)

(untitled) - Karthika, P.; Rajalakshmi, N.; Dhathathreyan, K. S. (Soft Nanosci. Lett., 2012)

(untitled) - Zhu, Y.; Murali, S.; Cai, W.; Li, X.; Suk, J. W.; Potts, J. R.; Ruoff, R. S. (Adv. Mater., 2010)

(untitled) - Tai, Z.; Yan, X.; Lang, J.; Xue, Q. (J. Power Sources, 2012)

Nanofibers of Conjugated Polymers - Sarac, A. S. (Pan Stanford, 2016)

(untitled) - Fennessey, S. F.; Farris, R. J. (Polymer, 2004)

(untitled) - Naraghi, M.; Arshad, S. N.; Chasiotis, I. (Polymer, 2011)

(untitled) - Zhou, Z.; Lai, C.; Zhang, L.; Qian, Y.; Hou, H.; Reneker, D. H.; Fong, H. (Polymer, 2009)

(untitled) - El-Hadi, A. M.; Mohan, S. D.; Davis, F. J.; Mitchell, G. R. (J. Polym. Res., 2014)

Continuous carbon nanofibers prepared from electrospun polyacrylonitrile precursor fibers - Fennessey, S. F. (University of Massachusetts, 2006)

(untitled) - Ismar, E.; Sarac, A. S. (Polym. Bull., 2017)

(untitled) - Ma, S.; Liu, J.; Liu, Q.; Liang, J.; Zhao, Y.; Fong, H. (Mater. Des., 2016)

(untitled) - Ouyang, Q.; Cheng, L.; Wang, H.; Li, K. (Polym. Degrad. Stab., 2008)

(untitled) - Liu, J.; Zhou, P.; Zhang, L.; Ma, Z.; Liang, J.; Fong, H. (Carbon, 2009)

(untitled) - Xue, T. J.; McKinney, M. A.; Wilkie, C. A. (Polym. Degrad. Stab., 1997)

(untitled) - Farsani, R. E.; Raissi, S.; Shokuhfar, A.; Sedghi, A. (Int. J. Mech. Aerosp. Ind. Mechatronic Manuf. Eng., 2009)

(untitled) - Ogawa, H.; Saito, K. (Carbon, 1995)

(untitled) - Mittal, J.; Bahl, O. P.; Mathur, R. B.; Sandle, N. K. (Carbon, 1994)

(untitled) - Clarke, A. J.; Bailey, J. E. (Nature, 1973)

(untitled) - Fu, Z.; Gui, Y.; Cao, C.; Liu, B.; Zhou, C.; Zhang, H. (J. Mater. Sci., 2014)

(untitled) - Park, O.-K.; Lee, S.; Joh, H.-I.; Kim, J. K.; Kang, P.-H.; Lee, J. H.; Ku, B.-C. (Polymer, 2012)

(untitled) - Bashir, Z. (Carbon, 1991)

Concise Polymeric Materials Encyclopedia - Salamone, J. C. (CRC Press, 1998)

(untitled) - Chang-qing, L. I.; Yang, X.; Hong-jiang, Z.; Xin, C.; Zhou-wen, H. E.; Liang-hua, X. U. (Trans. Mater. Heat Treat., 2015)

(untitled) - Chand, S. (J. Mater. Sci., 2000)

(untitled) - Mittal, J.; Konno, H.; Inagaki, M.; Bahl, O. P. (Carbon, 1998)

(untitled) - Sagirli, F. Z. E.; Kayali, E. S.; Sarac, A. S. (J. Electrochem. Soc., 2016)

(untitled) - Qu, D.; Shi, H. (J. Power Sources, 1998)

(untitled) - Ferrari, A. C. (Solid State Commun., 2007)

(untitled) - Kim, C.; Park, S.-H.; Cho, J.-I.; Lee, D.-Y.; Park, T.-J.; Lee, W.-J.; Yang, K.-S. (J. Raman Spectrosc., 2004)

(untitled) - Wang, Y.; Serrano, S.; Santiago-Aviles, J. J. (J. Mater. Sci. Lett., 2002)

(untitled) - Jawhari, T.; Roid, A.; Casado, J. (Carbon, 1995)

(untitled) - Rodriguez, N. M. (J. Mater. Res., 1993)

(untitled) - Sharma, C. S.; Katepalli, H.; Sharma, A.; Madou, M. (Carbon, 2011)

(untitled) - Gong, Y.; Li, D.; Fu, Q.; Pan, C. (Prog. Nat. Sci.: Mater. Int., 2015)

(untitled) - Manaf, N. S. A.; Bistamam, M. S. A.; Azam, M. A. (ECS J. Solid State Sci. Technol., 2013)

(untitled) - Raymundo-Piñero, E.; Kierzek, K.; Machnikowski, J.; Béguin, F. (Carbon, 2006)

(untitled) - Rubinson, J. F.; Kayinamura, Y. P. (Chem. Soc. Rev., 2009)